The Relevance of Islamic Educational Science to Modern Education: A Sharia Proof Review - Rajiman Habudu; Indah Baladil; Nurma Nurma; Jurdin Sapat (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Rapid transformations in contemporary education, driven by technological advancements, globalization pressures, and secular value shifts create multifaceted challenges for nurturing students' moral and spiritual growth. This situation calls for reinforcing core Islamic educational principles to ensure their continued applicability in today's learning environments. The study examines the alignment between Islamic pedagogy and modern educational frameworks by analyzing Sharia-based sources as epistemological foundations. Employing a qualitative approach through literature review, the research draws from Quranic verses, prophetic traditions, classical exegeses, scholarly books, and relevant peer-reviewed journals. Findings reveal substantial convergence between Islamic education's foundational concepts such as divine unity (tawhid), ethical conduct (adab), moral development (akhlak), and holistic human potential and modern education priorities, particularly character formation, intellectual-spiritual balance, and ethical strengthening among learners. These results affirm that Islamic education complements rather than conflicts with contemporary systems, serving as a values-based framework to navigate modernity's complexities. Thus, Islamic education must evolve contextually and adaptively integrating religious principles into curricula, teaching methodologies, and educational technologies to function as a comprehensive, identity-preserving solution.